Echocardiography diagnosis of myocardial infarction complications - N.D. Oryshchyn (Кардіохірургія та інтервенційна кардіологія)
Diagnosis and management of myocardial infarction complications are discussed in this article. These complications are associated with high level of mortality and surgery is a main treatment method. High level of suspicion and early diagnosis are essential for appropriate treatment and improvement of prognosis. Echocardiography is a main diagnostic method. Analysis of literature about contemporary management of mechanical complications of myocardial infarction has been performed, case reports are presented.